2021
DOI: 10.1109/access.2021.3133533
|View full text |Cite
|
Sign up to set email alerts
|

Event Camera Based Real-Time Detection and Tracking of Indoor Ground Robots

Abstract: This paper presents a real-time method to detect and track multiple mobile ground robots using event cameras. The method uses density-based spatial clustering of applications with noise (DBSCAN) to detect the robots and a single k-dimensional (k − d) tree to accurately keep track of them as they move in an indoor arena. Robust detections and tracks are maintained in the face of event camera noise and lack of events (due to robots moving slowly or stopping). An off-the-shelf RGB camera-based tracking system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…It entails using event data to extract features of different types (e.g., corners) and track them through time [ 21 , 22 , 23 ]. As for event-based object detection and tracking, most works have been application-specific, with few similarities overall [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. We categorize these works as either event-based or combined (i.e., using images and events) approaches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It entails using event data to extract features of different types (e.g., corners) and track them through time [ 21 , 22 , 23 ]. As for event-based object detection and tracking, most works have been application-specific, with few similarities overall [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. We categorize these works as either event-based or combined (i.e., using images and events) approaches.…”
Section: Related Workmentioning
confidence: 99%
“…A common approach to event-based object tracking is using clustering methods [ 25 , 26 , 31 , 34 ]. Clustering is an intuitive approach for event-based object tracking whenever there is no ego-motion applied to the camera, thus assuming that events are mainly generated around the moving objects.…”
Section: Related Workmentioning
confidence: 99%
“…A common approach to event-based object tracking is using clustering methods [26,31,25,34]. Clustering is an intuitive way for event-based object tracking whenever there's no ego-motion applied to the camera, thus assuming that events would mainly be generated around the moving objects.…”
Section: Event-based Object Trackingmentioning
confidence: 99%
“…In studies involving up to three robots, the experimental findings demonstrated 100% detection and tracking fidelity (as high as 93% for four robots) in the presence of event camera noise and robot stops. There was a gradual decline in the quality of detection and tracking as the lighting conditions changed [52]. Face Detection in Humanoid Robotic Systems as the third target reported in research works.Using design strategies like variable image scaling and simultaneous processing of many classifiers without integral picture creation, S. S. Lee et al ( 2016) created a fully pipelined architecture (Figure 6 f) that was implemented on the FPGA platform.…”
Section: P B Nithin Et Al (mentioning
confidence: 99%